Dilettante Theatricals: The elite amateur in the Georgian period. (2nd January 2020) - Hawley, Judith
Abstract : This article explores the clash of values between upper-class amateurs and professional actors at the turn of the nineteenth century. It focuses on the Pic Nic Society, an exclusive private theatrical club that performed in London from around 1801/2 until it was closed down by the big guns of the patent theatres, backed by the constant bombardment of the press. The battle of the Pic Nics was a case of one powerful interest group clashing with another. Both capital and cultural capital were at stake. In many ways, the Pic Nic Society has much in common with amateur theatre of the twentieth and twenty-first centuries. Yet, in key respects private theatricals were substantially different: the social elite were not locked into a system of alternating periods of work and free time determined by paid employment. The nature of private theatricals complicates the professional/amateur binary and raises simple but important questions: What values were associated with the amateur in that period? And what might this say to us now?